Double burden of malnutrition in Ghana: a holistic perspective - Casu, Laura; van den Bold, Mara; Diop, Loty; Aryeetey, Richard N. O.; Verstraeten, Roosmarijn (International Food Policy Research Institute, 2021)
In the context of a mounting burden of overweight and obesity and a persisting burden of undernutrition, double-duty actions (DDAs) (Figure 1) [1] are needed to tackle multiple forms of malnutrition simultaneously [2]. These include “interventions, programs and policies that have the potential to simultaneously reduce the risk or burden of both undernutrition (including wasting, stunting and micronutrient deficiency or insufficiency) and overweight, obesity or diet-related NCDs”. The World Health Organization has characterized the double burden of malnutrition (DBM) as “the coexistence of undernutrition (i.e. micronutrient deficiencies, underweight, and childhood stunting and wasting), along with overweight and obesity, or diet-related noncommunicable diseases, within individuals, households and populations, and across the life course” [3]. Coordinated action is, therefore, needed to ensure that a focus on the double burden is integrated into the design, implementation, monitoring and evaluation of policies and programs with potential double-duty effects across the life course, with intra- and inter-generational implications [1,3,4,5].